A fuzzy approach for speckle noise reduction in SAR images - Santoso, Ardhi W.; Bayuaji, Luhur; Pebrianti, Dwi; Suryanti, Awang; Lim, Tien Sze; Habibah, Lateh; Jasni, Mohamad Zain (IASE, 2016)
The Synthetic Aperture Radar (SAR) image has a high resolution and not influenced by weather conditions either day or night. SAR image with its advantages, is becoming popular than the optical image in earth observation using the remote-sensing techniques. However, the speckle noise that occurs in the SAR image causes difficulties in image interpretation. Thus, speckle noise reduction needs as prepossessing procedure prior to the use of the SAR images. The ideal speckle filter has the capability of reducing speckle noise without losing the information and preserving texture. Fuzzy approach has a good performance to reduce speckle noise in a medical image, which is occurred on a SAR image. It proposed a filter which is a combination of fuzzy with qualified existing filter that applied to SAR image, aimed at eliminating speckle noise while maintaining texture. The results showed that the proposed filter has better performance than commonly used filters such as the Mean, Median, Kuan, Lee, and Frost filters. The experiments conducted in a homogeneous area; forests, plantations and oceans from ALOS-PALSAR image in the area of Kuantan, Pahang, Malaysia.